Seizing investment opportunities to combat poverty and achieve sustainable development: An analytical study of Babylon investment authority projects 2021-2024 (Entrepreneurship Journal for Finance and Business, 2025)
The issues of combating poverty and sustainable development are among the most prominent challenges facing both developing and developed societies. Despite the efforts made by governments and international organizations, poverty still directly affects many countries, calling for the adoption of effective investment policies that improve economic and social conditions. Investment in combating poverty includes financial resources allocated to programs and policies aimed at improving the living standards of individuals in poor communities. This includes investments by governments and international organizations in sectors such as education, health, clean water, social finance, and job opportunities. Investing in combating poverty and achieving sustainable development is a long-term process that requires strong commitment from governments, international institutions, and civil society organizations alike. Investment in this area represents a cornerstone for achieving the Sustainable Development Goals, which are not limited to improving economic conditions but also extend to promoting social justice and reducing development gaps between different segments of society. The research addresses seizing investment opportunities in Babil Governorate for the period 2021-2024 across all governorate projects. Among the most important conclusions of the research is the need to increase investment in infrastructure and local labor, as well as investment in projects targeting the poorest segments of the governorate's population. The most important finding of the research is the significant impact of investment opportunities in combating poverty and improving the living conditions of the governorate's residents. This contributes to achieving sustainable development for Babil Governorate in particular and Iraq in general.